2019
DOI: 10.1002/lary.27319
|View full text |Cite
|
Sign up to set email alerts
|

Association of SLC26A4 mutations, morphology, and hearing in pendred syndrome and NSEVA

Abstract: Objective: To investigate the relations of monoallelic (M1), biallelic (M2), or the absence of mutations (M0) in SLC26A4 to inner ear morphology and hearing levels in individuals with Pendred syndrome (PS) or nonsyndromic enlarged vestibular aqueduct (NSEVA) associated with hearing loss.Methods: In a cohort of 139 PS/NSEVA individuals, 115 persons from 95 unrelated families had full genetic sequencing of SLC26A4, and 113 had retrievable images for re-assessment of inner ear morphology. The association between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 47 publications
1
25
0
1
Order By: Relevance
“…In this regard, in 2019, Mey et al demonstrated that individuals with two allele mutations of the Pendrin gene have a higher probability of having Mondini Malformation instead of isolated EVA [ 41 , 42 ]. Moreover, the same authors reported that SLC26A4 biallelic mutations were correlated with larger endolymphatic sac size [ 41 , 42 ]. Our findings confirmed the Mey et al thesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, in 2019, Mey et al demonstrated that individuals with two allele mutations of the Pendrin gene have a higher probability of having Mondini Malformation instead of isolated EVA [ 41 , 42 ]. Moreover, the same authors reported that SLC26A4 biallelic mutations were correlated with larger endolymphatic sac size [ 41 , 42 ]. Our findings confirmed the Mey et al thesis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, King et al in 2010, Rose et al in 2017, and Mey et al in 2019 demonstrated that patients with 2 mutated alleles showed worse thresholds and a tendency to progress faster than the patients with 1 or no mutated SLC26A4 alleles [ 22 , 41 43 ]. Also, an earlier onset of hearing loss in patients with biallelic mutations was described by those authors.…”
Section: Discussionmentioning
confidence: 99%
“…SLC26A4 c.2168A>G is a well-known recurring pathogenic variant with null function previously demonstrated in an in vitro study 42 . Although SLC26A4 variants that cause hearing loss have AR inheritance, a number of previous studies demonstrated EVA with monoallelic SLC26A4 variants 43 , 44 . These monoallelic SLC26A4 variants are proposed to cause EVA in combination with either yet-to-be identified pathogenic variants in noncoding regulatory regions of SLC26A4, as supported by analysis of EVA-recurrence rates 43 45 , or regulatory genes of SLC26A4 , such as EPHA2 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Sensorineural hearing loss is common in Turner, Richieri, Costa Pereira, Pendred and NSEVA syndromes. [22][23][24][25][26] Narrow nasal passages and adenoid overgrowth restricted the nasal obstruction, forcing the patient to breathe through an open mouth. Pathological breathing pathway through the open mouth may cause orthodontic disorders and malocclusions, and exacerbate the features of dry upper respiratory and laryngeal mucosa congestion.…”
Section: Discussionmentioning
confidence: 99%